2006
DOI: 10.1152/jn.00625.2005
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Nonlinearity During Recovery From Sequential Inhibition by Neurons in the Cat Primary Auditory Cortex

Abstract: Nakamoto, Kyle T., Jiping Zhang, and Leonard M. Kitzes. Temporal nonlinearity during recovery from sequential inhibition by neurons in the cat primary auditory cortex. J Neurophysiol 95: 1897-1907, 2006. First published December 7, 2005 doi:10.1152/jn.00625.2005. Auditory stimuli occur most often in sequences rather than in isolation. It is therefore necessary to understand how responses to sounds occurring in sequences differ from responses to isolated sounds. Cells in primary auditory cortex (AI) respond to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 32 publications
6
23
0
Order By: Relevance
“…Each panel is a ''binaural-level response area" (LRA), i.e., the response to the stimuli within the binaural matrix at a particular frequency. As found in earlier studies of LRAs in the inferior colliculus (Semple and Kitzes, 1987) and auditory cortex (Irvine et al, 1996;Nakamoto et al, 2004Nakamoto et al, , 2006Semple and Kitzes, 1993; 2005), these LRAs have a circumscribed focus of maximal responses to a subset of contiguous stimuli and a declining response to stimuli increasingly distant from the set of most effective stimuli. The set of LRAs is an estimate of the ''binaural response structure" (BRS) of the neuron.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Each panel is a ''binaural-level response area" (LRA), i.e., the response to the stimuli within the binaural matrix at a particular frequency. As found in earlier studies of LRAs in the inferior colliculus (Semple and Kitzes, 1987) and auditory cortex (Irvine et al, 1996;Nakamoto et al, 2004Nakamoto et al, , 2006Semple and Kitzes, 1993; 2005), these LRAs have a circumscribed focus of maximal responses to a subset of contiguous stimuli and a declining response to stimuli increasingly distant from the set of most effective stimuli. The set of LRAs is an estimate of the ''binaural response structure" (BRS) of the neuron.…”
Section: Resultssupporting
confidence: 59%
“…The methods used to obtain data were essentially identical to those used previously Nakamoto et al, 2006); additional details regarding experimental methods can be found in those publications.…”
Section: Methodsmentioning
confidence: 99%
“…This value is compatible with the neurophysiology data on un-anesthetized animals [1,[61][62][63][64][65] but rather shorter than the data (40-200 ms) on pentbarbiturateanesthetized animals [75][76][77].…”
Section: Ramification Of the Full-version Modelsupporting
confidence: 88%
“…We conclude that forward suppression probably includes contributions from both response-gain control and level-gain control. In contrast, forward suppression of responses to different binaural level combinations appears to act by response-gain control and not level-gain control (Nakamoto et al 2006;Zhang et al 2005). Although our free-field stimulus reached both ears, we did not independently vary binaural levels and thus do not know whether the binaural response properties of our neurons showed response-gain control, level-gain control, or both.…”
Section: Discussionmentioning
confidence: 97%